Dampak Hospitalisasi Pada Anak Dengan Typhoid Fever: Studi Kasus - Dessy Rindiyanti Harista; Susmawati Susmawati; Ahmad Zaini Arif; Lutfi Lutfi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Disease and hospitalization can be the crisis that a child encounters. Typhoid fever is an acute infectious disease of the digestive tract caused by Salmonella Typhi. Objective: The aim of this study was to identify the impact of hospitalization on children with typhoid fever.Methods: This research usea qualitative research with a case study approach. This research is a case study of nursing care for children with typhoid fever in the Cempaka Room, RSUD dr. Mohammad Zyn of Sampang Regency. Respondents in this case study were 2 children with Typhoid Fever.Results: The results of the study obtained the results from the objective data that the two children felt afraid and strange in the hospital. The subjective data shows that the parents of both children said they were worried about their child's condition. Parents and children experienced anxiety when the child was hospitalized.Conclusion: The impact of hospitalization for children causes fear, anxiety, due to unfamiliar environmental conditions and the treatment process by health workers. Meanwhile, the impact of hospitalization on parents can cause anxiety about the condition and development of their child's disease.